2021
DOI: 10.3390/logistics5030051
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potentials of Automation in Logistics and Supply Chain Management: Paving the Way for Autonomous Supply Chains

Abstract: The world of logistics is changing and entering a new era. The advance of digitalization and technologization enables new business models, increased process efficiencies, novel planning approaches, and much more but, on the downside, there is also the risk of being lost in the maelstrom of developments. Within these developments, the automation of logistics processes and ultimately the design of autonomous logistics systems is one of the most defining trends that has far-reaching consequences for the planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…These technologies are designed to learn and respond logically to massive amounts of data (28). Despite the fact that process automation is a major trend in logistics and supply chain management now and will become much more so in the near future, businesses are still apprehensive and face obstacles in implementing automated solutions (29). For example, Companies created "supplier risk towers," an autonomous supplier survey technique that allows for increased network awareness by calculating vulnerability scores at various levels (supplier, plant, and regional levels).…”
Section: Automationmentioning
confidence: 99%
See 1 more Smart Citation
“…These technologies are designed to learn and respond logically to massive amounts of data (28). Despite the fact that process automation is a major trend in logistics and supply chain management now and will become much more so in the near future, businesses are still apprehensive and face obstacles in implementing automated solutions (29). For example, Companies created "supplier risk towers," an autonomous supplier survey technique that allows for increased network awareness by calculating vulnerability scores at various levels (supplier, plant, and regional levels).…”
Section: Automationmentioning
confidence: 99%
“…For example, Companies created "supplier risk towers," an autonomous supplier survey technique that allows for increased network awareness by calculating vulnerability scores at various levels (supplier, plant, and regional levels). According to the survey results, this automation solution is a very effective crisis management strategy (30). We have gathered the qualitative data while conducting interviews with industry professionals in the supply chain domain, which is presented in Table 2.…”
Section: Automationmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/1359-8546.htm processes can evolve into autonomous processes, thereby bringing further value and enhanced resilience (Nitsche, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among the plethora of challenges arising from the digitalization process, the automation of informational processes in LSCM is a core challenge, as acknowledged by both academic research (Dotoli et al , 2019; Viale and Zouari, 2020; Frederico et al , 2019; Nitsche et al , 2021) and industry practice (Junge et al , 2019; Kersten et al , 2017). When equipped with enhanced decision-making abilities and artificial intelligence (AI), automated processes can evolve into autonomous processes, thereby bringing further value and enhanced resilience (Nitsche, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, new technologies enable collecting and sharing precise data and information easier and faster, and supply chains are increasingly working in a globally connected context. Previous research demonstrated the importance of ERP systems in supply chain performance (Nitsche et al, 2021;Palanivel & Karkuzhali, 2018;Ullah et al, 2018;Izhar et al, 2018;Shatat & Udin, 2012). Most of the processes of supply chain management in all its departments depend on the use of ERP systems, aside from Excel spreadsheets.…”
Section: Introductionmentioning
confidence: 99%